Initial Management Strategy for Pneumothorax and Hemothorax in the Emergency Department - Sayekti, Arinza Arum; Kurniadjaja, Muhammad Hanafi (Riviera Publishing, 2025)
Pneumothorax and hemothorax are emergency conditions that require rapid and appropriate intervention to prevent life-threatening complications. The emergency department (ED) plays a crucial role in providing initial management through early identification, patient stabilization, and determination of appropriate interventions. The purpose of this research is to comprehensively explain the initial management strategy for pneumothorax and hemothorax in the Emergency Department, from early detection and triage flow to appropriate medical intervention in accordance with emergency management standards. This study used the Systematic Literature Review (SLR) method to identify, analyze, and synthesize literature related to initial management strategies for pneumothorax and hemothorax in the emergency department. The review results show that the dominant themes in the literature are chest trauma patient management, emergency department intervention strategies, and clinical outcomes. Network visualization shows key words such as patient, trauma, pneumothorax, hemothorax, and emergency department. The overlay map indicates a shift in trends from a focus on basic trauma to the evaluation of complications and the latest management strategies, especially in the period 2021–2025. The density map confirms the high level of research attention on patient conditions and trauma, while the development of initial management strategies still needs to be explored further. The initial management strategy for pneumothorax and hemothorax in the emergency department is greatly influenced by a combination of clinical and non-clinical factors. A comparison with international guidelines such as ATLS shows gaps in implementation, particularly in terms of technology availability and protocol consistency.